Comment on the paper “The optical properties of quantum dots in anisotropic media” by Singh et al., J. Mol. Liq. 241 (2017) 1009–1012 - Roy, Joy Sankar [UNESP] (Elsevier, 2018)
The present comment concerns some doubtful results reported by Singh et al. [1].